5-ALA induced PpIX fluorescence spectroscopy in neurosurgery: a review - Gautheron, A.; Bernstock, J. D.; Picart, T.; Guyotat, J.; Valdés, P. A.; Montcel, B. (Frontiers in Neuroscience, 2024)
The review begins with an overview of the fundamental principles/physics underlying light, fluorescence, and other light-matter interactions in biological tissues. It then focuses on 5-aminolevulinic acid (5-ALA)-induced protoporphyrin IX (PpIX) fluorescence spectroscopy methods used in neurosurgery (e.g., intensity, time-resolved) and in so doing, describe their specific features (e.g., hardware requirements, main processing methods) as well as their strengths and limitations. Finally, we review current clinical applications and future directions of 5-ALA-induced protoporphyrin IX (PpIX) fluorescence spectroscopy in neurosurgery.